(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
Lead (Pb) is a substance that can cause serious damage to the brain and kidneys, soften bones, adverse effect to the reproductive system, and can be fatal. Long-term exposure to the substance can damage not only children, but also adults’ nervous systems. Lead does not belong into the category of toxic substances due to its effects on the human body. It is considered as a harmful substance. In this study, we analyzed lead concentration in liver and kidney of cattle, horse, sheep, and goat from the mining areas located in the Ulaanbadrakh, Zuunbayan, and Airag soums of Dornogovi province. As a result, the level of lead in the liver of sheep and goat Zuunbayan soum of Dornogovi province was slightly higher than in other soums. The content of heavy metals in water and soil samples did not exceed the international standard average.